2015
DOI: 10.1007/s40145-015-0164-y
|View full text |Cite
|
Sign up to set email alerts
|

Intense violet–blue emission and paramagnetism of nanocrystalline Gd3+ doped ZnO ceramics

Abstract: Nanocrystalline Zn 1x Gd x O (x = 0, 0.02, 0.04, 0.06, and 0.08) ceramics were synthesized by ball milling and subsequent solid-state reaction. The transmission electron microscopy (TEM) micrograph of as synthesized samples revealed the formation of crystallites with an average diameter of 60 nm, and the selected area electron diffraction (SAED) pattern confirmed the formation of wurtzite structure. A red shift in the band gap was observed with increasing Gd 3+ concentration. The photoluminescence of nanocrys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Although some experimental and DFT results conrmed the existence of room temperature ferromagnetism (RTFM) [38][39][40] property in Gd 3+ doped wurtzite ZnO, there are numbers of studies have established the absence of RTFM. 41,42 In addition to magnetic properties, one more attractive feature of the 4f ions doped ZnO nanocrystals is their optical response. Several experimental and theoretical investigations have reported that RE-doped ZnO can absorb ultraviolet (UV) light.…”
Section: Introductionmentioning
confidence: 99%
“…Although some experimental and DFT results conrmed the existence of room temperature ferromagnetism (RTFM) [38][39][40] property in Gd 3+ doped wurtzite ZnO, there are numbers of studies have established the absence of RTFM. 41,42 In addition to magnetic properties, one more attractive feature of the 4f ions doped ZnO nanocrystals is their optical response. Several experimental and theoretical investigations have reported that RE-doped ZnO can absorb ultraviolet (UV) light.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the valence band hole and conduction band electron undergo radiative recombination causing NBE emission at 387.6 nm. [ 25–27 ] Generally, emission in the visible region is due to crystallizing conditions and various intrinsic defects. Trivalent Gd 3+ ions can offer different transitions and exhibit blue emission [ 27,28 ] due to multiple impurity levels by multi‐ionization.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the progress of the crystallite size changed the hardness and elastic modulus significantly. 43 The oxidation change of cerium could be responsible for this reduction. 44 The mechanical properties of the hardness and elastic modulus parameters correlated for the pristine and Cu-doped CeO2 thin films.…”
Section: Resultsmentioning
confidence: 99%